Strategy in History and (versus?) in Economics: A Review of Lawrence Freedman's Strategy: A History - Dixit, Avinash (Journal of Economic Literature, 2014)
This essay reviews Lawrence Freedman's book Strategy: A History. The main themes—definitions, strategies in war, business, politics, and revolutions—are overviewed. The value of game-theoretic thinking for practical strategy is assessed. A critical discussion of some concepts and dichotomies emphasized by Freedman, e.g., strategy is governed by the starting point, not the end point, and of the role of stories and scripts in strategy, follows. (JEL A11, A12, C70, D74)